PERBEDAAN EDUKASI KONSUMSI SAYUR DAN BUAH PADA ANAK SD MENGGUNAKAN METODE CERAMAH DENGAN ALAT PERAGA DAN MEDIA AUDIOVISUAL - Septian Emma Dwi Jatmika; Firnadea Ekarizky Safrilia (GIZI INDONESIA, 2019)
The consumption of fruit and vegetables for children are quite less in Yogyakarta, it is around 93,6 percent Another effort to increase the consumption of vegetables and fruits are rising knowledge and attitude by health promotion with education methods used props and audiovisual media. This research was conducted to know the difference between lecture method with props and audiovisual media for children knowledge and attitude about the consumption of vegetables and fruits.This study was an experimental quasi study with a control group design of pretest and post test non-equivalent. The sampling research used purposive sampling with 55 students of 5 elementary grade. The test were use unpaired T tests.The result are shown that there was no different between lecturer methods with props and audiovisual media to children knowledge (p=0,073) and attitude (p=0,492) about consumed vegetable an fruits.